The brown bear (ursus arctos) in Bukovyna (Ukraine): distribution, habitats, diet, and morphological features = Ведмідь бурий (Ursus arctos) на Буковині (Україна): поширення, біотопи, живлення, морфологічні особливості - Volokh, Anatolii; Волох, Анатолій Михайлович; Tkachuk, Yuri (My University, 2025)
EN: In Bukovyna, the brown bear is constantly present in four forest districts, where it prefers old mountainous, cluttered coniferous and mixed forests. Some individuals cross mountain pastures and are found in old abandoned plum and apple orchards. The long border between Ukraine and Romania (243.7 km), where hunting has been banned for a long time, has had a significant positive impact on the bear population. This has contributed to an increase in numbers and allowed the animals to live undisturbed in the border forests and sometimes even cross the state border. Bears very rarely hibernate—no traces of them were seen during the harsh winter of 1995–1996. During the berry ripening season, bears visit forest glades searching for raspberries, blackberries, and other fruits. They eagerly consume beech nuts and acorns, hunt wild ungulates and attack domestic animals. Among wild mam mals, wild pigs dominate the bears’ diet (over 80%), with deer and roe deer occa sionally appearing. The bears sometimes kill cows and horses, and often feed on honey destroying apiaries. Despite the species being listed in the Red Book of Ukraine, the brown bear population in Chernivtsi Oblast continues to decline. The minimum population was recorded in 1963 (10 individuals), 1975 (16), and 2000 (17), and the maximum in 1990 (32), 1995 (35), and 2025 (36). The main reason for the decline in numbers is poaching, as evidenced by the periodic appearance of skins and bear cubs on the market. The largest brown bear population in Europe is found in the Carpathian Mountains in Romania, with an estimated population of 7500–10 000 individuals. Thanks to this, some individuals cross border fences and end up in various places in Bukovyna. Since the trophy quality of brown bears from the Carpathians is very high, limited trophy hunting has been introduced in Romania since 2016 to optimise their population. The trophy qualities of the skulls of four male brown bears from Bukovyna available to the authors were considered, three of which meet the requirements for obtaining gold medals according to the Madrid system. The bear population in Chernivtsi Oblast remains highly dependent on the rejuvenation of forests in the process of commercial logging and the abun dance of wild boars. /// UA: На Буковині ведмідь бурий постійно перебуває у чотирьох лісгоспах, де віддає перевагу ста рим гірським захаращеним листяним, хвойним та змішаним лісам. Окремі особини під час руху пересі кають полонини і трапляються у кинутих сливових та яблуневих садах. Значний позитивний вплив на поголів’я ведмедя створює велика довжина кордону між Україною та Румунією (243,7 км), де тривалий час було відсутнє полювання. Це сприяло зростанню чисельності і дало змогу тваринам безперешкодно мешкати у прикордонних лісах, а іноді й проникати через державний кордон. Ведмеді дуже рідко вда ються до зимової сплячки – їх слідів не бачили під час суворої зими 1995–1996 рр. В період дозрівання ягід ведмеді відвідують лісові галявини, де шукають малину, ожину та інші рослини. Вони охоче спо живають букові горішки та жолуді, добувають диких ратичних та нападають на свійських тварин. Серед диких ссавців у раціоні ведмедів домінують дикі свині (понад 80 %), іноді трапляються олені та сарни. Хижаки іноді вбивають корів та коней, а також часто живляться медом, руйнуючи пасіки. Попри зане сення виду до Червоної книги України, чисельність ведмедя у Чернівецькій обл. продовжує скорочува тися. Її мінімальна величина відмічена в 1963 (10 екз.), 1975 (16) і 2000 (17) роках, а максимальна — в 1990 (32), 1995 (35) і 2025 (36). Основною причиною зменшення чисельності є браконьєрство, про що свідчить періодична поява на ринках шкір і ведмежат. Найбільшим в Європі є угруповання бурого вед медя на території Карпат у Румунії, чисельність якого оцінюють у ~7500–10 000 особин. Завдяки цьому деякі особини долають прикордонні загорожі і потрапляють у різні місця Буковини. Оскільки трофейні якості ведмедя бурого з Карпат є дуже високими, у Румунії для оптимізації його чисельності з 2016 р. запроваджене обмежене трофейне полювання. Розглянуто трофейні якості доступних для авторів чере пів від чотирьох самців ведмедя бурого з Буковини, три з яких відповідають вимогам до здобуття золо тих медалей за Мадридською системою. Угруповання ведмедя у Чернівецькій обл. залишається дуже за лежним від омолодження лісів у процесі рубок головного користування та чисельності свині дикої.
Keywords: brown bear; habitats; diet; poaching; Carpathians; ведмідь бурий; місцезнаходження; живлення; браконьєрство; Карпати